Jaguncismo, coronelismo e poder público em Chapadão do Bugre - Marra, Bárbara Rodrigues Pereira (Universidade Federal de Catalão, 2022)
The objective of this work was to analyze the book Chapadão do Bugre from the perspective of space within literature, based on the theories of Bachelard (1989), Lins (1976), Borges Filho (2007), and on issues of space, territory and the social construction and cultural formation of historical Brazilian figures of the jagunço and the colonel, based on the theories of Candido (1972, 1977), Corpas (2006), Galvão (2018), emphasizing the importance of public power in this social format. The book, the corpus of this work, portrays, within the universe of literature, a reality lived for decades by the Brazilian population away from capitals and large centers, where there was little or no action by the public power and a lot of power on the part of the landowners colonels. . These controlled not only their employees, but the entire population in the vicinity of their lands. The destiny of becoming a jagunço often ended up being the only possible path for those who were born without land and without family, such as the protagonist José de Arimatéia, whose trajectory within the novel throughout Chapadão do Bugre, on the back of his mule Suede, guided the entire trajectory of this study.
Jaguncismo, coronelismo and public power in Chapadão do Bugre
Keywords: Chapadão do Bugre; Espaço na literatura; Jagunço; Coronel; Poder público; 7.08.00.00-6 Educação